Selection for improved virulence of Cryptophlebia peltastica nucleopolyhedrovirus (CrpeNPV) to False Codling Moth, Thaumatotibia leucotreta, by serial passage through a heterologous host - Iita, Petrus Paulus (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology)
The false codling moth (FCM), Thaumatotibia leucotreta (Meyrick) (Lepidoptera: Tortricidae) is endemic to southern Africa, and strongly associated with citrus. As South African citrus production is mainly for export to foreign markets, the market access risk due to the phytosanitary status of this pest is considerable and its control is therefore imperative. Various control measures as part of a rigorous integrated pest management (IPM) programme targeted against T. leucotreta have been effective at suppressing the pest in citrus, but there is still a growing need for continued improvement of the programme and augmentation of the available control options. Of these control options, biological control, particularly the use of Cryptophlebia leucotreta granulovirus (CrleGV-SA), is a key component of IPM in citrus orchards and it has been very successful at reducing T. leucotreta populations in the field for almost two decades. There is however, a growing need for more baculovirus variants with an improved virulence against T. leucotreta for a more efficient pest management system. The newly identified insect virus, Cryptophlebia peltastica nucleopolyhedrovirus (CrpeNPV) offers a unique opportunity for an additional biopesticide in IPM for control of T. leucotreta in the field. This study aimed to conduct serial passaging of CrpeNPV through a heterologous host, T. leucotreta, in order to determine the potential for improved virulence or speed of kill against it. In order to select for a variant of CrpeNPV with improved virulence against T. leucotreta, a high dose (LC90) of the virus OBs was used to perform 12 serial passages through T. leucotreta larvae in surface-dose bioassays. Whole genome sequencing and analysis of the passaged virus, along with restriction endonuclease profiling in silico was performed to determine if the genetic identity of the virus had changed during serial passage, in relation to the original virus. These analyses indicated that the dominant genotype of CrpeNPV was maintained following 12 serial passages through the heterologous host. The biological activity of the passaged virus, along with the original virus was evaluated against neonate T. leucotreta in surface-dose bioassays and compared. Results from dose-response bioassays showed that the virulence of CrpeNPV did not improve after 12 serial passages. The LC50 values of the passaged virus and the original virus were estimated at 1.96 × 104 and 1.58 × 104 OBs/ml, respectively, whereas the LC90 values were estimated at 3.46 × 104 OBs/ml for the passaged virus and 3.68 × 104 for the original virus. Similarly, the results from time-response bioassays showed that the speed of kill of CrpeNPV did not improve after 12 serial passages. The LT50 values of the passaged virus and the original virus were 88.44 hours (3 days and 16 hours) and 83.74 hours (3 days and 12 hours), respectively, whereas the LT90 values were 115 hours (4 days 19 hours) for the passaged virus and 102 hours (4 days 6 hours) for the original virus. The virulence and speed of kill of the passaged virus decreased significantly, in relation to the original virus. When the full genome of the passaged virus was sequenced and analysed, only a few SNPs were detected in the viral genome, in comparison to the original virus. No detectable difference in REN digestion patterns were observed following REN analysis of gDNA of the passaged virus with several restriction enzymes in silico. The results for this study suggest that CrpeNPV may already be optimally suited to the heterologous host as it persists under these conditions without significant changes to the genome. These results have positive implications for the genetic integrity of CrpeNPV as a potential biocontrol agent in the field. This study is the first to report the virulence selection of CrpeNPV by serial passage through a heterologous host, and also the first to record bioassay data in terms of dose response (or lethal concentration) against T. leucotreta second instars. The data obtained have added to the knowledge about interactions between CrpeNPV and its heterologous host, and may be fundamental to continued investigation into the effect of serial passage on pathogenicity and genetic diversity of CrpeNPV.
Keywords: Cryptophlebia leucotreta -- Biological control; Biological pest control agents; Citrus -- Diseases and pests; Baculoviruses; Cryptophlebia peltastica nucleopolyhedrovirus (CrpeNPV)